Microwave-Induced Synthesis of Some Novel Fungicidal Pyrazole Derivatives - Mishra, A. D. (Journal of Nepal Chemical Society, 2013)
A series of novel pyrazole derivatives have been synthesized from propanoyl hydrazine and aromatic aldehydes under microwave irradiations. The reaction leads to condensation in ethanolic solution to give corresponding hydrazones which undergo subsequent cyclisation to furnish pyrazole derivatives in presence of formic acid. The reaction rate is enhanced considerably by using microwaves with excellent yield as compared to conventional heating method. The reactions took 4-7 minutes for completion with 78-92% yield. All the synthesized pyrazole derivatives showed promising antifungal activities against Aspergillus niger and Aspergillus Flavus. Microwave-induced organic synthesis has been proved quite beneficial and eco-friendly method in terms of limited use of chemicals, short reaction time and good yield with higher degree of purity.DOI: http://dx.doi.org/10.3126/jncs.v30i0.9385Journal of Nepal Chemical Society Vol. 30, 2012 Page:  138-142 Uploaded date: 12/20/2013